Changing patterns of Insulin Resistance in Polycystic Ovary Syndrome - Laila, R; Mahmud, N; Nargis, M; Chowdhury, TA (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s):Aim of the study was to explore the changing patterns of insulin resistance in PCOS women. Methods: The study was conducted at CARE, department of Obstetrics and Gynecology and Biomedical Research Group, BIRDEM hospital. A total number of 103 PCOS women of 15- 36 years were included in the present study. They were grouped into NGT (n=68), IGT (n=30), type 2 DM (n=5) according to nature of glucose tolerance. Fasting and glucose stimulated insulin was measured. Results: In IGT group, fasting and glucose-stimulated insulin level were higher when compared with NGT, but no difference between type 2 DM and NGT group was found. Insulin-glucose ratio (after glucose load) was significantly lower in type 2 DM when compared with NGT group (p=0.049), but there was no difference of insulin-glucose ratio (fasting) between type 2 DM and NGT group. PCOS with IGT or Type 2 DM women were more insulin resistant than NGT group. (p=0.015, p=0.042 respectively). Conclusion: Insulin resistance is a major pathophysiologic feature of PCOS with IGT; however â cell secretory defect is associated with type 2 DM in these subjects. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 73-77